Setorização sedimentar do estuário do rio Mojuim, São Caetano de Odivelas/PA - BAIA, Lizandra Pantoja (2020)
The Mojuim river estuary, located in northeast Pará, flows into the Atlantic Ocean, it is influenced by fluvial and marine waters. The purpose of this study is identify the pattern of spatial distribution of bottom sediments and the recent deposition sectors, conditioned by fluvial and marine forcings, from the Mojuim river estuary (São Caetano de Odivelas/PA). We collected 117 samples of superficial sediment, with Van Veen grab sampler; the grain size of sediment samples is determined by the sieve method, and organic matter and carbonate by loss on ignition. Analytical data were treated statistically to propose the compartmentalization of the Mojuim estuary. The integration of sedimentological data and multivariate statistical techniques (Cluster analysis (Cluster) and principal component analysis (PCA), indicated that the Mojuim river estuary presents sediment ranging from very fine sand to mud, with low organic matter content (average 5.8%) and carbonate (average 2.4%). Furthermore, was possible to identify three depositional environments the Mojuim river estuary, a marine domain, with sandy sediment moderately selected, another with fluvial-estuarine domain, with muddy sediment poorly selected and a transitional domain.